THE SPECTRAL METHOD OF OPTIMAL FILTERING AND EXTRAPOLATION FOR JUMP-DIFFUSION MODELS - K. A. Rybakov (Научный вестник МГТУ ГА, 2016)
The article deals with the optimal filtering and extrapolation problems for non-stationary stochastic differential systems with a Poisson component. To find an approximate density of the observed object’s state vector the spectral method based on the representation of robust Duncan-Mortensen-Zakai equation and Kolmogorov-Feller equation solutions in the form of orthogonal series is used.